Seismic Performance of Modular Structures with Novel Steel Frame: Light Gauge Slotted Steel Stud Walls - Chao Gong; Dawei Sun; Qixian Chen; Yong Zhu; Mingxu Shang; Faqi Liu (Shock and Vibration)
Modular structures are premanufactured off-site and assembled on-site, leading to reduced on-site works and construction periods and improved quality compared to conventional prefabricated steel structures and reinforced concrete structures. Meanwhile, steel frame-light gauge slotted steel stud (LGSS) walls have been considered to be assembled into the modules due to their excellent thermal- and sound-insulation properties. These structural components will also contribute to the resistance of the modular system when subjected to lateral loads/actions, especially seismic actions. A finite element model was developed to investigate the seismic performance of high-rise modular steel structures with LGSS shear walls. Then, parametric studies were conducted to investigate the influences of the layouts of the LGSS shear walls and structure heights on the lateral stiffness, the deformation modes, and the stress states of the modular steel structures. Observed from the results of a ten-storey modular steel structure infilled with LGSS shear walls, the maximum storey drift reduced by 50.1–79.50% compared to the corresponding pure steel frame structure under the selected high-intensity seismic waves. The results indicate that the studied modular steel structure with LGSS shear walls possesses good seismic resistance and could be a practical and economical choice for future modular constructions.